Analysis of full-scale precast post-tension (FPP) girder for straddle monorail – Experimental and FEA study. (February 2022) - Suparp, Suniti; Joyklad, Panuwat; Sirisonthi, Athasit; Hussain, Qudeer
Abstract: The rapid growth of modern cities demands innovative answers to confront challenges linked with traffic congestions. Monorails can be an exceptional alternative to conventional skylines and subways thankfully to their excellent climbing abilities, lower noise, shorter constructions periods, and their capabilities to be adapted within limited spaces. Recently, Mass Rapid Transit Authority (MRTA) adopted monorail system to facilitate public in Bangkok's expanding neighborhoods. This study presents experimental results conducted on newly proposed three single span full-scale precast post-tension (FPP) girders for straddle monorail. FPP girders were tested under monotonic loads in service and ultimate load configurations. Results illustrated that proposed FPP girder system is adequate to suppress any cracking under service load conditions while limiting deflections well below corresponding permissible limits. Further, load-deflection response under ultimate load conditions revealed that sustained peak load was higher than the design load suggesting the appropriateness of design details and construction of proposed FPP girder systems to be effectively used in straddle monorail systems. Finite element analysis of FPP girder was also performed by using a computer program ATENA which is a computational tool for nonlinear engineering analysis of bridges and culverts. The finite element analysis results indicate that the computer program ATENA is well capable to predict the ultimate load carrying capacity, displacement and cracking patterns of FPP girder.